2021
DOI: 10.1097/ruq.0000000000000516
|View full text |Cite
|
Sign up to set email alerts
|

Superb Microvascular Imaging in Assessment of Synovitis and Tenosynovitis in Juvenile Idiopathic Arthritis

Abstract: The aim of this study is to evaluate the diagnostic utility of superb microvascular imaging (SMI) in assessment of synovitis/tenosynovitis in juvenile idiopathic arthritis in comparison to power Doppler ultrasound. Thirty juvenile idiopathic arthritis cases with active clinical findings and ultrasound features of effusion and/or tenosynovitis were further imaged with power Doppler and SMI. For classification of synovial inflammation, a semiquantitative scale (4 points) adopted by Outcome Measures in Rheumatolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Overall, 19 original studies of SMI application in rheumatology were found and 18 [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ] of them were analysed because we were not able to obtain the full text of one publication. The majority of the included studies were conducted in Japan [ 11 , 12 , 13 , 14 , 15 ], China [ 16 , 17 , 18 , 19 , 20 ], and Turkey [ 21 , 22 , 23 , 24 ]; single studies were conducted in Australia [ 25 ], Italy [ 26 ], South Korea [ 27 ] and the United Kingdom [ 28 ]. Reference screening provided three additional papers, but only one fulfilled the inclusion criteria and was included for analysis [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, 19 original studies of SMI application in rheumatology were found and 18 [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ] of them were analysed because we were not able to obtain the full text of one publication. The majority of the included studies were conducted in Japan [ 11 , 12 , 13 , 14 , 15 ], China [ 16 , 17 , 18 , 19 , 20 ], and Turkey [ 21 , 22 , 23 , 24 ]; single studies were conducted in Australia [ 25 ], Italy [ 26 ], South Korea [ 27 ] and the United Kingdom [ 28 ]. Reference screening provided three additional papers, but only one fulfilled the inclusion criteria and was included for analysis [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Wrist, knee, and hand (metacarpophalangeal—MCF, and proximal interphalangeal—PIF) joints were the most widely investigated joints. SMI was mostly compared with conventional PD [ 14 , 15 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ], and several studies included colour Doppler in their comparison methods [ 18 , 24 ]. A semi-quantitative scale (four-point 0–3 or 0–III grades by percentage, dots, or linear signals in the part of the synovial area) was adopted widely to assess vascularity using SMI and other Doppler techniques (14 out of 18 analysed studies).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, this result is in line with the current trend in improving more and more the sensitivity of depiction of increased or abnormal vascularity, particularly relevant in the overall much vascularised paediatric joint structures. 37 Conversely, US-guided injection guidelines were not included in the basic level content, but only in the intermediate and advanced ones. As expected, for intermediate and advanced courses, training on specific anatomic structures and their abnormalities was much more detailed than in the basic one.…”
Section: Discussionmentioning
confidence: 99%
“…It is a feasible imaging technique that can be performed with a higher sensitivity than PD imaging. 17…”
Section: Adultsmentioning
confidence: 99%
“…It is a feasible imaging technique that can be performed with a higher sensitivity than PD imaging. 17 Tenosynovitis of the foot and ankle tendons in PsA patients is a common finding, as is the dactylitic toe and in the latter case mostly affecting the flexor tendons. US and MRI are especially useful in monitoring disease progression and response to treatment.…”
mentioning
confidence: 99%